(untitled) (Bulletin of the Institute of Chemistry and Chemical Technology, 2022)
In this research work, the copper compound which exists in the form of sulfide in molybdenite concentrate (M1 and M2 samples) dissolved with a mixed solution of iron chlorides (FeCl3 and FeCl2), and it aimed to establish optimum conditions for increasing the content of molybdenum disulfide (MoS2) in the concentrate. The effect of various factors on copper dissolution from each concentrate was investigated and copper leaching in the optimized conditions was determined as 77.62% for sample M1 and 94.84% for sample M2. In addition, when studying the kinetics of copper dissolution in the temperature range of 343-373 K using the shrinking core model, the dissolution process for samples of the M1 and the M2 was controlled by chemical reaction (Ea=44.87 kJ/mol) and by diffusion model (Ea=18.62 kJ/mol), respectively. The content of copper in the solution after leaching was analyzed using ICPOES, and the composition of the solid phase was identified by XRD and SEM analysis. As a result of the experiments, the content of MoS2 in the solid residue increased to 90.10 % (M1 sample) and 88.59% (M2 sample). Молибденитийн баяжмалаас зэсийг төмрийн хлоридоор уусгах боломж Хураангуй: Энэхүү судалгааны ажлаар молибденитийн баяжмал (M1, M2)-д агуулагдах сульфидын хэлбэрт байгаа зэсийн нэгдлийг төмрийн хлоридууд (FeCl3 ба FeCl2)-ын холимог уусмалаар исэлдүүлэн уусгаж, баяжмал дахь молибдений дисульфид (MoS2)-ын агуулгыг нэмэгдүүлэх зохистой нөхцлийг тогтоохыг зорив. Баяжмал тус бүрээс зэсийг уусгах төрөл бүрийн хүчин зүйлийн нөлөөллийг судлан, уусгах процессын зохимжтой нөхцөл дэх зэсийн уусалт M1 дээжийн хувьд 77.62%, М2 дээжийн хувьд 94.84% байгааг тогтоосон. Түүнчлэн зэсийн уусалтын кинетикийг 343-373 K температурын хязгаарт shrinking core загвар ашиглан судлахад зэс уусах процесс М1 дээж (Ea=44.87 кЖ/моль) химийн урвалаар, M2 дээж (Ea=18.62 кЖ/моль) диффузийн загвараар явагдаж байгааг тогтоов. Уусгалтын дараах уусмал дахь зэсийн агуулгыг ICPOES, хатуу фазын найрлагыг XRD, SEM аргуудаар тодорхойлсон. Туршилтын эцсийн үр дүнд уусгалтын хатуу үлдэгдэл дэх MoS2-ын агуулга 90.10 % (М1) ба 88.59% (М2) хүртэл нэмэгдсэн. Түлхүүр үг: молибдений дисульфид, исэлдүүлэлт, уусгалт, халькопирит.